The investigation of the inflammation hypothesis in children diagnosed with ASD and ADHD using complete blood count variables - Aslan, Cihan; Nalbant, Kevser; Ünal, Dilek; Kılıç, Buket (Acta Medica, 2026)
Objective: This study aims to compare the inflammation-related complete blood count (CBC) variables in children diagnosed with Autism Spectrum Disorder (ASD) and Attention Deficit Hyperactivity Disorder (ADHD). Materials and Methods: Retrospective data on CBC values and Childhood Autism Rating Scale (CARS) scores for 30 children with ASD and 30 with ADHD, aged 60-108 months, were retrieved from hospital automation systems. Inflammatory-related CBC parameters, including hemoglobin (Hb), red cell distribution width (RDW), neutrophil, lymphocyte, monocyte, and platelet counts, mean cell volume (MCV), mean platelet volume (MPV), neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), and platelet-to-lymphocyte ratio (PLR), were compared between the two diagnostic groups. This study has a retrospective and cross-sectional design. Results: Children with ASD exhibited significantly higher platelet counts (p=0.003; t=3.052; d=0.788) and PLR (p = 0.044; Z = -2.011; r = 0.259), whereas MPV was significantly lower (p=0.029; t=-2.241; d=-0.579) compared to children with ADHD. No significant differences were observed in other parameters. Additionally, a negative correlation was identified between CARS scores and RDW values in children with ASD (p = 0.035, r = -0.387). Conclusion: Although ASD and ADHD are two neurodevelopmental disorders in which inflammation has been investigated in their pathophysiology, the inflammatory processes may differ between the two conditions. Future genetic and biochemical studies related to platelets in ASD may provide further insights into this area.